SDH mutations in cancer. - Bardella, C; Pollard, P; Tomlinson, I (2011)
The SDHA, SDHB, SDHC, SDHD genes encode the four subunits of succinate dehydrogenase (SDH; mitochondrial complex II), a mitochondrial enzyme involved in two essential energy-producing metabolic processes of the cell, the Krebs cycle and the electron transport chain. Germline loss-of-function mutations in any of the SDH genes or assembly factor (SDHAF2) cause hereditary paraganglioma/phaeochromocytoma syndrome (HPGL/PCC) through a mechanism which is largely unknown. Owing to the central function of SDH in cellular energy metabolism it is important to understand its role in tumor suppression. Here is reported an overview of genetics, clinical and molecular progress recently performed in understanding the basis of HPGL/PCC tumorigenesis.